HUBUNGAN RENDAHNYA SELF-EFFICACY DENGAN PROKRASTINASI AKADEMIK SISWA PADA PEMBELAJARAN QUR’AN HADIS - Khaironi, Ika; M. Samsul Hady; Imron Rossidy; Ainun Jariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the phenomenon of academic procrastination in learning the Qur'an Hadith in the madrasa environment, although ideally Islamic educational institutions emphasize discipline, responsibility, and sincerity in learning. The behavior of postponing tasks is not only related to technical aspects such as time management, but also related to students' psychological factors, especially self-efficacy or belief in one's ability to complete academic tasks. Based on this, this study aims to analyze the relationship between low self-efficacy and students' academic procrastination in learning the Qur'an Hadith. This study uses a quantitative ex post facto approach with a correlational type. Data were collected through self-efficacy and academic procrastination questionnaires given to respondents, then analyzed using a simple correlation test to see the direction and strength of the relationship between variables. The results showed that there was a significant relationship between low self-efficacy and academic procrastination with a significance value of 0.001 (<0.05) and a correlation coefficient that showed a strong relationship with a positive direction of 0.705. These findings indicate that the lower a student's self-efficacy, the higher the tendency for academic procrastination, and vice versa. Theoretically, these results align with Albert Bandura's emphasis on how an individual's belief in their abilities influences their actions, effort, and persistence in completing tasks. Therefore, this study confirms that self-efficacy plays a significant role in reducing academic procrastination and provides important implications for strengthening learning strategies focused on enhancing student self-confidence in the context of Qur'anic and Hadith education.